2012
DOI: 10.1111/j.1476-5381.2012.01958.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial F0F1‐ATP synthase is a molecular target of 3‐iodothyronamine, an endogenous metabolite of thyroid hormone

Abstract: BACKGROUND AND PURPOSE3-iodothyronamine (T1AM) is a metabolite of thyroid hormone acting as a signalling molecule via non-genomic effectors and can reach intracellular targets. Because of the importance of mitochondrial F0F1-ATP synthase as a drug target, here we evaluated interactions of T1AM with this enzyme. EXPERIMENTAL APPROACHKinetic analyses were performed on F0F1-ATP synthase in sub-mitochondrial particles and soluble F1-ATPase. Activity assays and immunodetection of the inhibitor protein IF1 were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 89 publications
1
18
0
Order By: Relevance
“…This has subsequently been verified by numerous laboratories (Mühlhaus et al, 2014;Cöster et al, 2015;Chiellini et al, 2017), with 3IT also shown to act as an agonist at TAAR2 (Babusyte et al, 2013;Cichero and Tonelli, 2017) and as an inverse agonist at TAAR5 (Dinter et al, 2015c). 3IT is promiscuous, however, and also interacts with high affinity at a 2 -adrenoceptors (Regard et al, 2007;Dinter et al, 2015b), b-adrenergic receptors (Meyer and Hesch, 1983;Kleinau et al, 2011;Dinter et al, 2015a), muscarinic acetylcholine receptors (Laurino et al, 2016), transient receptor potential cation channel subfamily M member 8 ion channels (Khajavi et al, 2015;Lucius et al, 2016), various monoamine and organic anion transporters (Snead et al, 2007;Panas et al, 2010), and molecular target(s) within mitochondria, including the F 1 -F 0 ATP synthase (Cumero et al, 2012) and possibly complex III (Venditti et al, 2011). 3IT also tightly binds to the plasma protein apolipoprotein B-100 .…”
Section: E 3-iodothyronaminementioning
confidence: 99%
“…This has subsequently been verified by numerous laboratories (Mühlhaus et al, 2014;Cöster et al, 2015;Chiellini et al, 2017), with 3IT also shown to act as an agonist at TAAR2 (Babusyte et al, 2013;Cichero and Tonelli, 2017) and as an inverse agonist at TAAR5 (Dinter et al, 2015c). 3IT is promiscuous, however, and also interacts with high affinity at a 2 -adrenoceptors (Regard et al, 2007;Dinter et al, 2015b), b-adrenergic receptors (Meyer and Hesch, 1983;Kleinau et al, 2011;Dinter et al, 2015a), muscarinic acetylcholine receptors (Laurino et al, 2016), transient receptor potential cation channel subfamily M member 8 ion channels (Khajavi et al, 2015;Lucius et al, 2016), various monoamine and organic anion transporters (Snead et al, 2007;Panas et al, 2010), and molecular target(s) within mitochondria, including the F 1 -F 0 ATP synthase (Cumero et al, 2012) and possibly complex III (Venditti et al, 2011). 3IT also tightly binds to the plasma protein apolipoprotein B-100 .…”
Section: E 3-iodothyronaminementioning
confidence: 99%
“…In vitro studies provided evidence that T 1 AM can activate with high-affinity G protein-coupled receptors, including trace amine-associated receptor 1 (Scanlan et al 2004, Zucchi et al 2006) and possibly a2-adrenoceptors (Regard et al 2007). In addition to these receptors, T 1 AM also interacts with plasma membrane and vesicular biogenic amine transporters (Snead et al 2007) as well as different mitochondrial targets (Venditti et al 2011, Cumero et al 2012.…”
mentioning
confidence: 99%
“…This is underscored by a recent study examining mitochondria effects of T1AM whereby low physiologic levels in cardiomyocytes enhanced ADP-stimulated mitochondrial respiration while higher levels inhibited F o F 1 -ATP synthase activity [39]. T1AM is also observed to interact with Complex III via antimycin A in mitochondria, decreasing O 2 consumption and increasing H 2 O 2 release in mitochondria of cultured hepatocytes, which may partially explain observed decrease in O 2 consumption in vivo [39]. Most recently, Ghanian et al [4] found that T1AM is able to modulate cellular redox state (NADH/FAD ratio) in mouse tissue-specifically and in a dose specific manner [4]; interestingly this effect was divergent between dosage and tissue type.…”
Section: Mitochondria and Cellular Redoxmentioning
confidence: 99%
“…T1AM affects a broad range of physiological processes and organ systems. The physiology of T1AM appears to be complex as its effects at similar dosages can have opposing effects in different organs [4] or opposing effects on the same system at different dosages [39]. The specific physiologic response appears to be further complicated by differing responses to duration and dosage pattern; acute administration of high dosages of T1AM (50 mg/kg) results in rapid induction of hypothermia [1] and a drop in metabolic rate [36], but chronic low dosages of T1AM (10 mg/kg repeated over 8 days) results in elevated lipolysis and sustained reduction in body mass [3].…”
Section: Discussionmentioning
confidence: 99%